Evaluation for equitable development results - and Segone, M (UNICEF, 2011)
This document is made up of a range of Evaluation Working Papers (EWP) focused on evaluation for equitable development. Put together by evaluation specialists they present strategic evaluation findings, lessons learned and innovative approaches and methodologies. Part 1:Evaluation and equity Evaluation to accelerate progress towards equity, social justice and human rights 2 Human rights and gender equality in evaluation 13 When human rights is the starting point for evaluation 25 Strengthening Equity- focused evaluations through insights from feminist theory and approaches 39 Decolonizing evaluation in a developing world. Implications and cautions for Equity-focused evaluations 59 Part 2: Methodological implications for Equity-focused evaluations Methodological issues to design and implement equity-focused evaluations 86 Developmental evaluation for Equity-focused evaluations 102 Systems thinking and Equity-focused evaluations 115 Methodological challenges in using programme theory to evaluate pro-poor and equity-focused programmes by Patricia Rogers, Royal Melbourne Institute of Technology University and Richard Hummelbrunner, Independent consultant 142 Case Study and equity in Evaluationby Saville Kushner, University of the West of Englan 172 Values-Engaged Evaluationsby Jennifer Greene, University of Illinois at Urbana-Champaign 192 Part 3: Examples of Equity-focused evaluations Evaluating the contribution of UNDP to equity-focused public policies in Brazil and China 210 Using a human rights approach to evaluate ILO’s discrimination strategy 222 CONEVAL experience in evaluating interventions for Indigenous populations in Mexico 244 UNICEF supported evaluations with elements of equity-focused evaluations 258